Late and non-payments issues in the Malaysian construction industry : perspective of building material suppliers / Mohd Fisal Ishak, Kartina Alauddin and Mohd Shahrol Hafiz Ibrahim - Mohd Fisal, Ishak; Kartina, Alauddin; Mohd Shahrol Hafiz, Ibrahim (Universiti Teknologi MARA, Perak, 2019)
Payment in the Malaysian construction industry has generally been an issue of concern. Late and non-payment problem is endemic in construction and needs to be addressed. The aim of this study is to investigate the issues related to late and non-payment based on the building materials suppliers’ perspective. Questionnaires were distributed to suppliers of building materials in the Klang Valley. Findings from the study shows the main cause of late and non-payment is the paymaster’s poor financial management while the main effect of late and non-payment is problem with the cash flow. The most recommended possible solution to cope with the issue is for the paymaster to conduct training on financial and cash flow management to the management team in the company.